ANALISIS KONTRIBUSI PROGRAM SL-PTT TERHADAP PENINGKATAN PRODUKSI PADI DI KECAMATAN PERCUT SEI TUAN, KABUPATEN DELI SERDANG, PROVINSI SUMATERA UTARA - Gustina Siregar (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2013)
The first aim of this study was to determine the effect of SL - PTT programe ( improved varieties, seed quality, seeding, tillage, planting, watering later, fertilizing, weed control in an integrated, pest and disease control in an integrated , harvest and post- harvest ) to the increase in production rice; both to know the difference before and after the rice production program SLPTT. The population in this study were all farmers who participate in the program the SL - PTT rice growing season in 2012 ( approximately 300 farmers in the district Percut Sei Tuan ). The sample is a portion of the population that is considered to have a number of desirable characteristics with 20-25 % of the population so that 50 samples are drawn at random. Data analysis techniques used method of Multiple Linear Regression Analysis and Test average difference. Statistically Test results obtained multiple R value of 0.99 and an F - count 1034,281> F - 2:49 table at 95% confidence level ( α = 0.05 ), in the sense that there is a significant effect. In Partial test, the best variety (X1) Seed treatment only grade ( X2 ) and Planting ( X5 ) is significant while the other variables are not significant. Based on the test results generated Beda average rice production for farmers who follow the program after the SL - PTT larger than that rice production for farmers before the program SLPTTKeywords : SL-PTT Programe, increase, production, rice, percut sei tuan